2016
DOI: 10.1103/physrevlett.116.216402
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Confined Metal from the Mott InsulatorSr3Ir2O7

Abstract: The spin-orbit Mott insulator Sr 3 Ir 2 O 7 provides a fascinating playground to explore insulator-metal-transition driven by intertwined charge, spin, and lattice degrees of freedom. Here we report high-pressure electric resistance and resonant inelastic X-ray scattering measurements on single-crystal Sr 3 Ir 2 O 7 up to 63-65 GPa at 300 K. The material becomes a confined metal at 59.5 GPa, showing metallicity in the ab-plane but an insulating behavior along the c-axis. Such unusual phenomenon resembles the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 65 publications
8
84
0
Order By: Relevance
“…The first feature is ascribed to the single magnon excitation [48,49], while the second feature is ascribed to the transition of a hole from the j eff = 1/2 ground state to the j eff = 3/2 band, in agreement with previous works on the sister compound Sr 2 IrO 4 [31,63]. The pressure dependence at room temperature of the latter excitation has been already investigated by Ding et al, who have found that the peak position changes by at most ∼ 15% from ambient pressure to approximately 65 GPa, while the width does not undergo a significant change [64]. We note that magnetic excitations could not be resolved in the RIXS spectra measured by Ding et al [64] not only because the measurements were carried out at room temperature, but also because of the spurious signal from the sample environment extending up to several hundreds of meV.…”
Section: Resultssupporting
confidence: 91%
“…The first feature is ascribed to the single magnon excitation [48,49], while the second feature is ascribed to the transition of a hole from the j eff = 1/2 ground state to the j eff = 3/2 band, in agreement with previous works on the sister compound Sr 2 IrO 4 [31,63]. The pressure dependence at room temperature of the latter excitation has been already investigated by Ding et al, who have found that the peak position changes by at most ∼ 15% from ambient pressure to approximately 65 GPa, while the width does not undergo a significant change [64]. We note that magnetic excitations could not be resolved in the RIXS spectra measured by Ding et al [64] not only because the measurements were carried out at room temperature, but also because of the spurious signal from the sample environment extending up to several hundreds of meV.…”
Section: Resultssupporting
confidence: 91%
“…19,20 One of the anomalous properties inherent to (Sr 1−x La x ) 3 Ir 2 O 7 is the appearance of a structural distortion below a characteristic temperature T S . 11 This lattice distortion seemingly competes with antiferromagnetism and is suggestive of a secondary signature of an otherwise hidden electronic instability.…”
Section: Introductionmentioning
confidence: 99%
“…1 for an overview. Pulsed single photon streams are produced from an InAs/GaAs quantum dot cooled to 4 K and deterministically coupled to a micropillar cavity (36,37). Under pulsed resonant laser excitation (38), a clear Rabi oscillation of the resonance fluorescence single-photon counts as a function of pump power is shown in Fig The single-photon stream is then deterministically de-multiplexed into 20 spatial modes using fast optical switches, arranged in a tree-like structure (see Fig.…”
mentioning
confidence: 99%